Distal regulation, silencers, and a shared combinatorial syntax are hallmarks of animal embryogenesis - Cornejo-Páramo, Paola; Roper, Kathrein; Degnan, Sandie M.; Degnan, Bernard M.; Wong, Emily S. (Genome Research, 2022)
The chromatin environment plays a central role in regulating developmental gene expression in metazoans. Yet, the ancestral regulatory landscape of metazoan embryogenesis is unknown. Here, we generate chromatin accessibility profiles for six embryonic, plus larval and adult stages in the sponge Amphimedon queenslandica. These profiles are reproducible within stages, reflect histone modifications, and identify transcription factor (TF) binding sequence motifs predictive of cis-regulatory elements operating during embryogenesis in other metazoans, but not the unicellular relative Capsaspora. Motif analysis of chromatin accessibility profiles across Amphimedon embryogenesis identifies three major developmental periods. As in bilaterian embryogenesis, early development in Amphimedon involves activating and repressive chromatin in regions both proximal and distal to transcription start sites. Transcriptionally repressive elements (“silencers”) are prominent during late embryogenesis. They coincide with an increase in cis-regulatory regions harboring metazoan TF binding motifs, as well as an increase in the expression of metazoan-specific genes. Changes in chromatin state and gene expression in Amphimedon suggest the conservation of distal enhancers, dynamically silenced chromatin, and TF-DNA binding specificity in animal embryogenesis.
10.1101/gr.275864.121